Usersâ Satisfaction in Using the Central Library of IAIN Antasari Banjarmasin - Hajiri, Muhammad Isra (Universitas Airlangga, 2016)
Library as one of the public services attempts to give the users satisfaction, especially in providing the documents and information. Usersâ satisfaction is highly dependent on the quality of a product. Library product is the collection and service provided. The study aims to find out the usersâ satisfaction toward the collection and the services of UPT of Library Center of IAIN Antasari Banjarmasin. The method used in the study was descriptive with quantitative approach. The sampling used Taro Yamane theory with the precision degree of 10. There were 99 respondents consist of 95 students, 4 lectures and staffs, and 1 person outside university. The result showed that the library usersâ satisfaction on the completeness of collection in the central library of IAIN Antasari is in quite satisfied category since the average score is 3.22 which is on the interval scale of 2.62-3.42. Usersâ satisfaction on the current collection is 3.25. Therefore, it can be concluded that the usersâ satisfaction on the current collection is on the interval scale of 2.62-3.42 which is in the scale of quite satisfied. Library usersâ satisfaction on the librarian service is quite satisfied since the average score of the respondent satisfaction is 3.43 which is in the interval scale of 3.43-4.23. The average score of usersâ satisfaction on the service facility of the library is 3.53, so it can be concluded that the library usersâ satisfaction on the service facility in the central library of IAIN Antasari is on the interval scale of 3.43-4.23 which is quite satisfied. The total average score of library usersâ satisfaction on the collection and service in the central library of IAIN Antasari is 3.42 which is in the quite satisfied category.